El Flaneur y la Flanerie en las crónicas modernistas latinoamericanas: Julián del Casal, Amado Nervo, José Martí, Manuel Gutiérrez Nájera y Arturo Ambrogi. - Cuvardic García, Dorde (2012)
Flanerie finds in Enrique Gómez Carrillo and Rubén Darío two of its best examples in Latin American Modernism. However, Manuel Gutiérrez Nájera, Amado Nervo, Julián del Casal, José Martí, José Enrique Rodó and Arturo Ambrogi also produced texts depicting classic flanerie such as watching urban spaces as social theater, creating pintoresque escenarios or cuadros, or focusing on commercial spaces or public festivities. As a decadent, Julian del Casal, represents an aristocratic and dissenchanted perspective, whereas Marti is a clear example of the paradox between acknowledging American progress and the rejection of their moral values, in contradiction against the latino soul.